Rapid Screening of 22 Polycyclic Aromatic Hydrocarbons Residues in Vegetable Oils by Gas Chromatography-Electrostatic Field Orbitrap High Resolution Mass Spectrometry - Meng, Zhijuan; Fan, Sufang; Yuan, Xiaoxuan; Li, Qiang; Huang, Yunxia; Niu, Lisha; Shi, Guohua; Zhang, Yan (Frontiers in Nutrition, 2022)
A method for simultaneous determination of 22 polycyclic aromatic hydrocarbons (PAHs) residues in vegetable oils by gas chromatography-electrostatic field orbitrap high resolution mass spectrometry (Orbitrap GC-MS) was established. The samples were vortexed with acetonitrile, centrifuged at 8 000 r/min for 5 min, and frozen at -70 ℃ for 10 mins. The extracts of upper layer were poured out, dried with nitrogen at 40 ℃, redissolved in dichloromethane, and measured by Orbitrap GC-MS. The matrix interference in vegetable oil could be effectively removed by determining the accurate mass number of target compounds under the full scan mode. 6 typical vegetable oil samples (soybean oil, sesame oil, peanut oil, olive oil, rapeseed oil, sunflower oil) were used for method validation. The calibration curve displayed good linearity in the range of 1-100 ng/mL, with correlation coefficients greater than 0.9950. The limits of detection were in the range of 0.10-0.60 μg/kg, and the limits of quantification were in the range of 0.35-2.00 μg/kg. The average spiked recoveries of 22 PAHs in 6 matrices at 5, 50 and 100 μg/kg levels were 76.4-115.4%, and the average relative standard deviations were 1.8-10.8%. The results showed that 22 PAHs were detected in 6 types of 90 edible vegetable oil samples in the Chinese market by this method. Meanwhile, the abundance of light PAHs (LPAHs) was higher than that of heavy PAHs (HPAHs), and its relative contribution of LPAHs to the total PAHs was higher. All levels of BaP conformed to the Chinese requirement of upper limit, 10 μg/kg. However, 13.3% and 11.1% of the samples exceeded the maximum limits of BaP and PAH4 set by EU, 2 and 10 μg/kg, respectively. The total concentrations of 22 PAHs (defined as PAH22) varies greatly among different oil species, and the average PAH22 contents were listed in descending order as follows: peanut oil > sesame oil > olive oil > rapeseed oil > soybean oil > sunflower seed oil. The established method effectively avoided interference from large amounts of lipids and pigments. Therefore, the method is simple, sensitive and suitable for rapid screening and confirmation of PAHs in vegetable oil.